The Phalangopsidae crickets (Orthoptera, Grylloidea) of the Seychelles Archipelago: Taxonomy of an ecological radiation - Hugel, Sylvain; Warren, Ben H.; Desutter-Grandcolas, Laure (Zootaxa, 2021)
The Phalangopsidae crickets (Grylloidea) of the Seychelles are examined following extensive field sampling on several main islands of the archipelago (Mahé, Silhouette, Praslin, La Digue). Despite the small area of these islands, six genera (12 species) are documented, including one new genus and five new species. The type species of the genus Seychellesia Bolivar, 1912 is transferred to the genus Paragryllodes Karny, 1909 as Paragryllodes nitidula (Bolivar, 1912) n. comb. The other species described in Seychellesia are transferred to the genus Seselia Hugel & Desutter-Grandcolas, n. gen., as Seselia longicercata (Bolivar, 1912) n. comb. and Seselia patellifera (Bolivar, 1912) n. comb. Two new species are also described in the genus Seselia Hugel & Desutter-Grandcolas, n. gen., Seselia coccofessei Hugel & Desutter-Grandcolas, n. gen., n. sp. (type species of the genus) and Seselia matyoti Hugel & Desutter-Grandcolas, n. gen., n. sp. The genera Phaeogryllus Bolivar, 1912 and Phalangacris Bolivar, 1895 are redescribed, including Phalangacris ferlegro Hugel & Desutter-Grandcolas, n. sp. and Phalangacris sotsote Hugel & Desutter-Grandcolas, n. sp. that are new to science. The genus Gryllapterus Bolivar, 1912 is redescribed and transferred from the Landrevinae (Gryllidae) to the Cachoplistinae (Phalangopsidae). New tribes are defined for the genus Paragryllodes (Paragryllodini Hugel & Desutter-Grandcolas, n. tribe) on the one hand, and for Seselia Hugel & Desutter-Grandcolas, n. gen., Phalangacris, Phaeogryllus and Gryllapterus (Seselini Hugel & Desutter-Grandcolas, n. tribe) on the other, using morphological characters and the results of molecular phylogenetic studies (Warren et al. 2019). Phaloria (Papuloria) insularis (Bolivar, 1912) (Phaloriinae) is redescribed and restricted to Mahé, and its calling song is documented for the first time, while Phaloria (Papuloria) bolivari Hugel & Desutter-Grandcolas, n. sp. is newly described from Silhouette. Identification keys are proposed for the genera of Seselini Hugel & Desutter-Grandcolas, n. tribe, and for the species of Seselia Hugel & Desutter-Grandcolas, n. gen. and Phalangacris. The confusion between the Mogoplistidae Ornebius succineus Bolivar, 1912 and the Phalangopsidae Heterotrypus succineus Bolivar, 1910 is discussed, and the name Subtiloria succineus (Bolivar, 1912) considered a nomen nudum.